"Nodal Gap" Induced by the Incommensurate Diagonal Spin Density Modulation in Underdoped High-Tc Superconductors. (21st July 2015) - Zhou, Tao; Gao, Yi; Zhu, Jian-Xin
Abstract : Recently it was revealed that the whole Fermi surface is fully gapped for several families of underdoped cuprates. The existence of the finite energy gap along thed -wave nodal lines (nodal gap) contrasts the common understanding of thed -wave pairing symmetry, which challenges the present theories for the high-T c superconductors. Here we propose that the incommensurate diagonal spin-density-wave order can account for the above experimental observation. The Fermi surface and the local density of states are also studied. Our results are in good agreement with many important experiments in high-T c superconductors.